PENGARUH KOMUNIKASI DAN BUDAYA KERJA TERHADAP PRODUKTIVITAS KARYAWAN NAFAZ COLLECTION (Jurnal Riset Manajemen dan Akuntansi, 2023)
This study aims to determine the effect of simultaneously and partially Communication and Work Culture on Employee Productivity in Nafaz Collection. The research method used in this study is a quantitative method with a census approach. The population in this study amounted to 55 employees at Nafaz Collection. The type of data used in this study is primary data obtained through questionnaires. The data testing technique used in this study uses the validity test, reliability test and classic assumption test. Data analysis in this study used multiple regression analysis using SPSS software version 25. The results of this study indicate that communication and work culture simultaneously have a significant effect on employee productivity in nafaz collection. Communication partially has a significant effect on Employee Productivity in the Nafaz Collection and Work Culture partially has a significant effect on Employee Productivity in the Nafaz Collection.